Variable Expression of Cre Recombinase Transgenes Precludes Reliable Prediction of Tissue-Specific Gene Disruption by Tail-Biopsy Genotyping - Schulz, Tim J. (Public Library of Science, 2007)
The Cre/loxP-system has become the system of choice for the generation of conditional so-called knockout mouse strains, i.e. the tissue-specific disruption of expression of a certain target gene. We here report the loss of expression of Cre recombinase in a transgenic mouse strain with increasing number of generations. This eventually led to the complete abrogation of gene expression of the inserted Cre cDNA while still being detectable at the genomic level. Conversely, loss of Cre expression caused an incomplete or even complete lack of disruption for the protein under investigation. As Cre expression in the tissue of interest in most cases cannot be addressed in vivo during the course of a study, our findings implicate the possibility that individual tail-biopsy genotypes may not necessarily indicate the presence or absence of gene disruption. This indicates that sustained post hoc analyses in regards to efficacy of disruption for every single study group member may be required.